Nanomedicine : a soft matter perspective - Pan, Dipanjan (CRC Press, Taylor & Francis Group, 2015)
"This book provides a broad introduction to matters for nano-medicinal application. It covers comprehensive information regarding "soft" nanoscopic objects with prerequisite features for different imaging modalities. The book also offers a general introduction to the various drug delivery systems and their opportunities from chemistry, materials, biology and nanomedical standpoint. The book provides a broad introduction to the field and the sub field, with a deeper discussion on the individual modalities for molecular imaging, expanded in four chapters"--Resumé vydavatele
Keywords: nanomedicína; molekulární zobrazování; nanomedicine; molecular imaging; kolektivní monografie; collective monographs